Psychological and Social Problems of Adult Female Victims After Sexual Assault - Gölge, Zeynep Belma; Yavuz, Mustafa Fatih; Korkut, Songül; Kahveci, Sevilay (The Bulletin of Legal Medicine, 2014)
Objective: This study aimed to investigate the prevalence of psychological and social problems faced by female victims after rape and additionally the impact of also being a victim of childhood sexual abuse in Turkey, where opportunity of getting medical and psychological support for sexual assault for victims is limited and legal process lasts for years.Method: Participants consisted of 93 female rape victims who were examined by the Second Specialization Board of State Council of Forensic Medicine.  An interview form, which is developed in order to investigate socio-demographic features, assault charactersitics, psychological and social problems of victim, Post Traumatic Diagnostic Scale (PTDS)  and Childhood Trauma Questionnaire were applied for the investigation.Results:  61.3 % of victims were diagnosed with post traumatic stres disorder (PTSD) and 54.8% of victims had sexual dysfunctions caused by the sexual assault. 68.8 % of victims reported that they were exposed to negative social reactions. 70,3% of victims who were exposed to negative social reactions met diagnostic criteria for PTSD while only 41,4% of people who were not exposed to negative social reactions met diagnostic criteria for PTSD. Difference between groups was analyzed with chi squre method and there is significant difference between them ( X2:7.04, df:1, p
Keywords: rape; trauma; ptsd; self-mutilation